The Effect of Regional Factors on the Mental Health Status of Frontline Nurses and Patients With COVID-19 During COVID-19: The Role of Depression and Anxiety - Shanguang Zhao; Fangfang Long; Xin Wei; Xin Wei; Jianqing Tuo; Hui Wang; Xiaoli Ni; Xin Wang (Frontiers Media S.A., 2022)
At the end of 2019, Wuhan, Hubei Province, China, experienced the ravages of Coronavirus disease 2019 (COVID-19). In a few months, infected people rose to tens of thousands. This study aimed to explore the mental health status of military nurse personnel assisting (non-Hubei area) in the fight against COVID-19 and local nurse personnel (in the Wuhan area), as well as the differences in mental health status between nurses and COVID-19 patients that provide a reference basis for psychological crisis intervention. A convenience sampling method was used to select frontline nurses and COVID-19 patients (sample size 1,000+) from two mobile cabin hospitals from January to March 2020. The questionnaire consists of socio-demographic information, Patient Health Questionnaire 9 (PHQ-9), Generalized Anxiety Disorder 7 (GAD-7), General Mental Health Service Questionnaire and Work Intensity and Physical Status Questionnaire. The results showed that depression was present in 117 nurses (19.73%) and 101 patients (23.33%) with PHQ-9 scores >10; anxiety was present in 60 nurses (10.12%) and 54 patients (12.47%) with GAD-7 >10. The anxiety and depression levels of nurses in Wuhan area were higher than those in non-Hubei area. The differences in PHQ-9 and GAD-7 scores were also statistically significant (p < 0.001) when comparing patients from different regions, with anxiety and depression rates of 30.19 and 16.04% in local patients and 16.74 and 9.50% in foreign patients. The comparison between nurses and patients showed that the nurses were more depressed than the patients, while the patients were more anxious. Local nurses in Wuhan had a higher workload intensity than aid nurses (77.72 vs. 57.29%). Over 95% of frontline nurses and patients reported that they had not received any form of psychological counseling before the COVID-19 outbreak. 12.87% (26/194) of frontline nurses in Wuhan had a history of taking hypnotic drugs. However, fewer patients (16/212, 7.55%) took medication than frontline nurses. Anxiety and depression levels were far higher among local nurses and patients in Wuhan than in non-Hubei areas. The nurses had higher levels of depression, while the patients had higher anxiety levels. Providing targeted mental health services to healthcare professionals and patients is necessary when experiencing the impact of a major event.